On the Influence of PV Cell and Diode Configurations on the Performance of a CPVT Collector: A Comparative Analysis - João Gomes; Juan Pablo Santana; Damu Murali; George Pius; Iván P. Acosta-Pazmiño (Energies)
Concentrating photovoltaic-thermal (CPVT) collectors use reflective surfaces to focus sunlight onto a smaller receiver area, increasing thermal energy output while maintaining annual energy efficiency. Ray-tracing simulations are employed in this study using Tonatiuh to optimise the characteristics of the Double MaReCo (DM) collector, which is an improved version of the commercially available Solarus Power Collector (PC). Focused on enhancing electrical performance, the photovoltaic (PV) cell configurations are varied on the bottom side of the receiver, while the top-side PV cells remain constant. The study also analyses the influence of diodes and transparent gables on the annual solar irradiance received by the PV cells. From the analysis, it is observed that the specific annual irradiance received by the PV cells in the DM collector with transparent gables is nearly 64% more compared to that of the PC counterpart. It is also observed that the transparency of gables becomes significant only when the whole area of the receiver is covered by PV cells. With the goal of improving performance while lowering the cost and complexity of the DM collector, the study investigates various collector design characteristics that may shed more light on optimising the current model.